Electrical Discharge Machining of Al (6351)-5% SiC-10% B4C Hybrid Composite: A Grey Relational Approach. (13th May 2014) - Suresh Kumar, S.; Uthayakumar, M.; Thirumalai Kumaran, S.; Parameswaran, P.; Mohandas, E.
Abstract : The goal of the present experimental work is to optimize the electrical discharge machining (EDM) parameters of aluminum alloy (Al 6351) matrix reinforced with 5 wt.% silicon carbide (SiC) and 10 wt.% boron carbide (B4 C) particles fabricated through the stir casting route. Multiresponse optimization was carried out through grey relational analysis (GRA) with an objective to minimize the machining characteristics, namely electrode wear ratio (EWR), surface roughness (SR) and power consumption (PC). The optimal combination of input parameters is identified, which shows the significant enhancement in process characteristics. Contributions of each machining parameter to the responses are calculated using analysis of variance (ANOVA). The result shows that the pulse current contributes more (83.94%) to affecting the combined output responses.